2004
DOI: 10.1037/0021-9010.89.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Job Satisfaction-Performance Relationship: The Complexity of Attitudes.

Abstract: The present article argues that organizational researchers tend to adopt an overly simplistic conceptualization and operationalization of job satisfaction (and job attitudes in general). Specifically, past research has failed to examine the affective-cognitive consistency (ACC) of job attitudes and the implications this has for the strength of the attitude and its relationship with behavior (e.g., job performance). Results from Study 1 suggest ACC is a significant moderator of the job satisfaction-job performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
171
2
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(202 citation statements)
references
References 50 publications
11
171
2
9
Order By: Relevance
“…These findings support the results of research Schleicher et al (2004) found that there is a relationship OCB on the performance so that organizational effectiveness is achieved. The results of confirmatory factor analysis showed that the OCB primary reflected by the willingness to follow the development and progress made, to do something useful for others for the sake of progress organizations, attended the meeting, earnestly follow the rules, perform basic tasks, submit reports and work plans earlier than supposed and is willing to take the time to help others has been helping leaders to improve organizational performance by both H 7 : OCB employees can be improve organizational effectiveness OCB has a positive and significant effect on organizational effectiveness with a p-value of 0.004 > 0.05 and a coefficient standardized by 0.607, this coefficient indicates that the better OCB, the higher organizational effectiveness (supported H 7 ).…”
Section: Resultssupporting
confidence: 82%
“…These findings support the results of research Schleicher et al (2004) found that there is a relationship OCB on the performance so that organizational effectiveness is achieved. The results of confirmatory factor analysis showed that the OCB primary reflected by the willingness to follow the development and progress made, to do something useful for others for the sake of progress organizations, attended the meeting, earnestly follow the rules, perform basic tasks, submit reports and work plans earlier than supposed and is willing to take the time to help others has been helping leaders to improve organizational performance by both H 7 : OCB employees can be improve organizational effectiveness OCB has a positive and significant effect on organizational effectiveness with a p-value of 0.004 > 0.05 and a coefficient standardized by 0.607, this coefficient indicates that the better OCB, the higher organizational effectiveness (supported H 7 ).…”
Section: Resultssupporting
confidence: 82%
“…While the concept of satisfaction may be considered an attitude towards the product (i.e. like the concept of job satisfaction in a work context; e.g., Schleicher et al, 2004), joy, pleasure and fun (which appear to be used largely synonymously in the usability literature) represent emotions, which, in contrast, have a clear focus on the internal state of the user. Emotions are increasingly considered to be an important issue in consumer product design, as a rising number of publications have paid testimony to (e.g., Helander and Khalid, 2006;Norman, 2004a;Brave and Nass, 2003).…”
Section: Subjective User Evaluations and Emotionsmentioning
confidence: 99%
“…The research of Coelho Jr. (2009) demonstrated that satisfaction influences individual job performance; however, this influence depends on the unit in which the employee is allocated. In reviewing the recent literature, studies have pointed to a positive predictive relationship between job satisfaction and job performance, with emphasis in most of these studies, on the task performance (Coelho Jr. & Borges-Andrade, 2011;Edwards, Bell, Arthur Jr., & Decuir, 2008;Fischer, 2003;Schleicher, Watt, & Greguras, 2004;Sy, Tram, & O'Hara, 2006).…”
Section: Job Satisfaction As a Predictor Of Individual Performancementioning
confidence: 99%